Adsorption of basic red 46 dye using sea mango (cerbera odollam) activated carbon
The limited source of raw materials for production of activated carbon has increased the price of commercial activated carbon price. Due to the presence of lignin and cellulose in sea mango make it as new potential for activated carbon. Sea mango activated carbon was prepared by chemical activation using potassium hydroxide (KOH) at different carbonization temperatures, which are 500ºC (AC500) and 600ºC (AC600) under nitrogen (N2) gas flow. The activated carbon prepared together with sea mango precursor (SMP) was characterized using Scanning Electron Microscope (SEM) and Brunaer Emmet Teller (BET) for surface morphology and specific surface area, respectively. The result showed that the surface of AC500 and AC600 has undergone some alteration where some new pores were developed. The specific surface area measured for SMP, AC500 and AC600 were 0.03 m2/g, 108.79 m2/g and 451.87m2/g, respectively. Fourier Transform Infrared Spectroscopy (FTIR) use to analyse functional group showed band transition between the three samples which indicated that chemical transformation had occurred during activation process. Analysis of Total Ash Content (TAS) has shown that the ash content increased in both AC500 (38.97%) and AC600 (41.82%) compared to SMP (2.53%) whereas AC500 has better yield compared to AC600. In order to study the performance of sea mango activated carbon, AC600 was further used in adsorption of Basic Red 46 dye in batch process. The effects of operating parameters, initial pH solution, adsorbent dosage, initial dye concentration and adsorption temperature were varied where the result obtained indicated that all parameters have played important roles in the adsorption process. High initial dye concentration has resulted in low adsorption of Basic Red 46 dye with the best initial pH solution was 11. It was found that the removal of Basic Red 46 dye increased with the increasing amount of adsorbent dosage and adsorption temperature. Interaction between parameters was studied using Response Surface Methodology (RSM). The optimum parameters were recorded at 150 mg/L initial dye concentration, initial pH solution of 11.00 and 1.00 g/L adsorbent dosage with R2 of 0.9943. Moreover, from the isotherm and kinetic analysis conducted, the results showed a monolayer adsorption as the data fitted well on Langmuir isotherm model and pseudo-second-order kinetic model with R2 values closed to 1.